ASSESSMENT OF ANTIOXIDANT POTENTIAL AND ANTIGENOTOXICITY ANALYSIS THROUGH HYDROGEN PEROXIDE-INDUCED OXIDATIVE STRESS IN TERMINALIA PANICULATA ROTH - P, ASWATHI; ERNEST THOPPIL, JOHN (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The present study is mainly focused on the antigenotoxicity and antioxidant potential of the fruit extract of an important dye yielding plant Terminalia paniculata Roth. Methods: Genoprotective activity of the fruit extract was studied by Allium cepa root tip assay. Three modes of treatment were used to perform the antigenotoxicity, that is, pre-treatment, post-treatment, and simultaneous treatment. For the study of antioxidant potential, four different assays were performed. Results: Antigenotoxicity studies revealed the protective role of the extract in chromosomal aberrations induced by 2% hydrogen peroxide (H2O2) on A. cepa root tip meristem. The fruit extract showed a significant modulatory effect by means of an inhibition percentage and also it showed a characteristic reversing of chromosomal aberrations induced by H2O2. While in the case of antioxidant activity, the plant extract showed an appreciable antioxidant potential. Four different assays were used to determine the antioxidant potential of T. paniculata. Of these 2,2-diphenyl-1-picryl-hydrazyl-hydrate radical scavenging activity revealed almost equal effect to that of the standard. Conclusions: In the present investigation, it has been found that the important dye yielding plant T. paniculata has a significant role in various commercial industries such as food, cosmetics, clothes, and pharmaceutics due to its efficient protective role.